Developing Guidelines for the Use of Powerpoint in the Psychology Classroom - Zellhoefer, Ashley S.; Murken, Nathaniel B.; Hustedt, Benjamin D. (My University, 2010)
PowerPoint is widely used in college classrooms. Whether it is useful is controversial. Despite industry suggestions for "effective" PowerPoint use, critics argue that these suggestions are based neither on evidence nor on common sense. In response to critiques and in reaction to their own curiosity, researchers are beginning to evaluate empirically PowerPoint's effects on students' memory and comprehension, but these efforts appear unsystematic. In this poster we will sketch the literature, briefly summarize our research, and derive preliminary recommendations that we hope are more evidence-based than previous recommendations.
Color poster with text.
Keywords: Audiovisual education--Handbooks, manuals, etc.; Media programs (Education)--Handbooks, manuals, etc.; Microsoft PowerPoint (Computer file)--Handbooks, manuals, etc.; Psychology--Study and teaching--Handbooks, manuals, etc.; Posters